2017
DOI: 10.7567/jjap.56.085506
|View full text |Cite
|
Sign up to set email alerts
|

Van der Waals epitaxy of GaN-based light-emitting diodes on wet-transferred multilayer graphene film

Abstract: We experimentally investigated the possibility of using multilayer graphene to solve large mismatch problems between sapphire and nitride and further studied the effects of a multilayer graphene interlayer on the optical and electrical properties of LEDs. For the subsequent growth of 3-µm-thick GaN on AlN, multilayer graphene helps release stress and effectively removes cracks. In addition, multilayer graphene increases the diffraction of the substrate surface as determined from the increase in optical transmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
25
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…22 Based on these measurements, we estimate that the residual stress of AlN is significantly reduced from 0.87 GPa to 0.25 GPa with the assistance of Gr. 23 The high-resolution transmission electron microscopy (HRTEM) image of the AlN/Gr/NPSS interface shows the presence of an approximately 0.7-nm-thick Gr layer [dark area in Fig. 2(d)] that keeps its original layered structure after 1200 C AlN growth owing to the excellent stability.…”
mentioning
confidence: 99%
“…22 Based on these measurements, we estimate that the residual stress of AlN is significantly reduced from 0.87 GPa to 0.25 GPa with the assistance of Gr. 23 The high-resolution transmission electron microscopy (HRTEM) image of the AlN/Gr/NPSS interface shows the presence of an approximately 0.7-nm-thick Gr layer [dark area in Fig. 2(d)] that keeps its original layered structure after 1200 C AlN growth owing to the excellent stability.…”
mentioning
confidence: 99%
“…[ 19–22 ] In addition, GaN grown by MOVPE with oxygen‐plasma pretreatment are all Ga‐lattice‐polarity while N‐lattice‐polarity has never been reported until now to the best of our knowledge. [ 23–29 ] In contrast to Ga‐polarity GaN, N‐polarity one offers a different atomic configuration in chemical activity, which not only allows the access to kinetic space in epitaxy that is not normally attainable on Ga‐polarity surface, but also enables the fabrication of a variety of novel device structures. [ 30,31 ] Furthermore, since N‐polarity InGaN, which acts as quantum well in the case of visible light emitting devices, stands higher growth temperature than Ga‐polarity one and thus the In composition can be higher at the same growth temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Because the weak van der Waals binding between graphite and GaN films can relax the requirements for lattice matching between two material systems, mechanically exfoliated graphite can be used as an ideal substrate for GaN growth. To date, many studies have reported the successful growth of GaN films on graphene, but the graphene they used is almost always prepared by chemical vapor deposition (CVD) or graphitization of SiC substrates [ 12 15 ]. Such graphene layers have abundant step edges and defects that act as nucleation sites to induce film growth.…”
Section: Introductionmentioning
confidence: 99%